SCIENTIFIC RESEARCH WORK OF STUDENTS AND THEIR APPROBATION - Makhanov M, Маханов М (Рroblems of engineering and professional education, 2023)
This article provides information about the organization of scientific-research workof students, the formulation of the results of scientific work and testing. Learning to read the article allows the main direction sand methods of scientific-research work of students, requires short time to test the results of the work.